Cytotoxicity of doxorubicin-conjugated poly[N-(2-hydroxypropyl)methacrylamide]-modified γ-Fe2O3 nanoparticles towards human tumor cells - Plichta, Zdeněk; Kozak, Yulia; Panchuk, Rostyslav; Sokolova, Viktoria; Epple, Matthias; Kobylinska, Lesya; Jendelová, Pavla; Horák, Daniel (Beilstein journal of nanotechnology, 2018)
Doxorubicin-conjugated magnetic nanoparticles containing hydrolyzable hydrazone bonds were developed using a non-toxic poly[N-(2-hydroxypropyl)methacrylamide] (PHPMA) coating, which ensured good colloidal stability in aqueous media and limited internalization by the cells, however, enabled adhesion to the cell surface. While the neat PHPMA-coated particles proved to be non-toxic, doxorubicin-conjugated particles exhibited enhanced cytotoxicity in both drug-sensitive and drug-resistant tumor cells compared to free doxorubicin. The newly developed doxorubicin-conjugated PHPMA-coated magnetic particles seem to be a promising magnetically targeted vehicle for anticancer drug delivery.
Keywords: doxorubicin; cytotoxicity; poly[N-(2-hydroxypropyl)methacrylamide]; nanoparticles; magnetic